Design of mini CNC machine - Nur Suraini, Hashim (2012)
This thesis presents the design of Mini CNC Machine. This machine has 2axes, namely the Xand Y axis. Mini CNC machine is a small CNC machine that can operate like a normal CNC machine with a limited area of the machining. The objectives of this project are to develop the mini CNC Machine and to develop the software to control the machine. This thesis describes the development of the machine and the criteria needed to build the machine. The Mini CNC Machine is initially sketched by referring to the criteria that was decided. The criteria are the travel path length, type of linear motion, type of linear drive, motor and controller, and type of material that used. This machine’s travel on the X axis is 15cm and Y axis is 15cm. The linear motion was used is a round linear rail and the linear drive used was a sliding element, lead nuts and lead screws. The motor used is a stepper motor with specification 2.1V and 3.0A. The frame material used is aluminium. This material is used because it is light in weight, easy to handle and machine and it is rust proof. The design was sketched using SolidWork software. For the next step is developing the wiring for motor and develop the program to control the stepper motor. The ULN 2803 is used to convert the signal from parallel port to specific winding energizing sequences to step the motor. The Visual Basic software is used to program the motor movement.